Characterizing isomiR variants within the microRNA‐34/449 family. Issue 5 (28th February 2017) - Mercey, Olivier; Popa, Alexandra; Cavard, Amélie; Paquet, Agnès; Chevalier, Benoît; Pons, Nicolas; Magnone, Virginie; Zangari, Joséphine; Brest, Patrick; Zaragosi, Laure‐Emmanuelle; Ponzio, Gilles; Lebrigand, Kevin; et al.
Abstract : miR‐34/449 microRNAs are conserved regulators of multiciliated cell differentiation. Here, we evidence and characterize expression of two isomiR variant sequences from the miR‐34/449 family in human airway epithelial cells. These isomiRs differ from their canonical counterparts miR‐34b and miR‐449c by one supplemental uridine at their 5′‐end, leading to a one‐base shift in their seed region. Overexpression of canonical miR‐34/449 or 5′‐isomiR‐34/449 induces distinct gene expression profiles and biological effects. However, some target transcripts and functional activities are shared by both canonical microRNAs and isomiRs. Indeed, both repress important targets that result in cell cycle blockage and Notch pathway inhibition. Our findings suggest that 5′‐isomiR‐34/449 may represent additional mechanisms by which miR‐34/449 family finely controls several pathways to drive multiciliogenesis. Abstract :